Overlay of residual herbicides in rice for improved weed management. (June 2019) - Osterholt, Matthew J.; Webster, Eric P.; Blouin, David C.; McKnight, Benjamin M.
Abstract: A study was conducted at the Louisiana State University Agricultural Center's H. Rouse Caffey Rice Research Station in 2017 and 2018 to evaluate a prepackaged mixture of clomazone plus pendimethalin applied delayed preemergence (DPRE) or POST within an herbicide residual overlay with saflufenacil, clomazone, or quinclorac. POST applications included penoxsulam or halosulfuron in combination with the second residual application. No differences were observed in barnyardgrass control (92% to 98%) at 14 days after treatment (DAT). At 42 DAT, barnyardgrass treated with clomazone plus pendimethalin in combination with either clomazone or quinclorac at either timing was controlled 95% to 96%. However, when saflufenacil was applied PRE, regardless of the POST herbicide or when saflufenacil was applied POST with halosulfuron, barnyardgrass control was reduced to 78% to 81%, compared with 95% to 96% with the control with all other residual combinations. Yellow nutsedge and rice flatsedge control increased when treated with halosulfuron compared with penoxsulam across all evaluation dates. At 28 and 42 DAT, texasweed treated with saflufenacil PRE, regardless of POST applications, was controlled 83% and 87%, respectively, and this was greater control than provided by clomazone or quinclorac applied PRE regardless of POST herbicide program.